Photovoltaics in Micro Grids through Distribution Networks - Sateesh, P.; Rajesh, Asam; Shaik, Masma; Ashalatha, K.; Narsetti, Hemanthkumar; Sivakumar, P.; Prasad, T. Ram; Rajesh, M. (New Horizons of Science, Technology and Culture Vol. 1, 2025)
A micro grid is defined as a series of electrical loads, elements of generated power supply and storage elements that, connected to the electric grid by means of a single point of connection, are all linked through a strategy that manages both the flow of energy within the grid as well as the interchange of power with the main supply grid. First, a micro grid is an integration platform for local generation, storage and demand, all placed within a local distribution grid. Local generation is typically found at low voltage levels, and it is generally known as microgeneration due to its low scale. Photovoltaic systems are frequently integrated into microgrids, which are controlled local electricity distribution networks that serve both electricity consumers and renewable energy producers. a microgrid, and it was seen that there are four main characteristics that must be present in every microgrid. A microgrid is an integration platform for distributed generation and loads; it can work either in grid-connected or islanded mode; it is characterised by active operation; and it can be found in multiple scales. Then, the electrical power grid layers and the potential benefits that microgrids can provide to both the main grid and consumers were identified. Among these benefits, higher resiliency, efficiency and modularity were found. From fundamental definitions to modelling and control of AC and DC microgrids to the use of adaptive protection in microgrids, this course covers a wide range of topics related to DC and AC microgrids. The study will help gain knowledge of a number of topics pertaining to microgrid implementation and technology, including markets, distribution network types, smart grid and virtualpower plants, control strategies, and componentry. Among the components, the power electronics interface operation and control receive particular attention. The study will shed light on the DC microgrids' benefits and drawbacks.